Village Apparatus Performance in Population Administration Services in Village - Mohamat Riski Rosandy; Isnaini Rodiyah (Indonesian Journal of Cultural and Community Development, 2023)
The purpose of the study was to analyze and describe the performance of village officials in population administration services in Senepo Village, Slahung District, Ponorogo Regency. The method used by the descriptive researcher with a qualitative approach the data collection techniques used were interviews, observation and documentation with one key informant and four informants, namely the Village Head Village Secretary Head of Service and two community users of population administration services. Data analysis techniques in this study are data collection data reduction, data presentation and conclusion drawing The results of this study indicate that the Performance of Village Apparatus in Population Administration Services in Senepo Village, Slahung District Ponorogo Regency. the quality of work related to aspects of the skills and expertise of the apparatus has been maximized. The employees are always quick to serve the community and prioritize the interests of the community so that the community is satisfied with the services provided. Timeliness related to administrative services in Senepo Village is on time. Punctuality is the responsibility of every village apparatus to complete population administration required by the community. The capabilities in question are based on education skills, work experience that provide benefits. If these capabilities are successfully executed and completed properly, then the individual human resources are considered qualified. Quality human resources are human resources who are reliable, independent, and professional in carrying out their main duties and functions at work